Combination of pegylated interferon‐alpha and nucleos(t)ide analogue treatment enhances the activity of natural killer cells in nucleos(t)ide analogue experienced chronic hepatitis B patients. (24th July 2020) - Pang, X.; Zhang, L.; Liu, N.; Liu, B.; Chen, Z.; Li, H.; Chen, M.; Peng, M.; Ren, H.; Hu, P.
Summary: A combination of pegylated interferon‐alpha (peg‐IFN‐α) and nucleos(t)ides analogue (NA) therapy can effectively reduce hepatitis B surface antigen (HBsAg), especially in NA‐experienced chronic hepatitis B (CHB) patients. However, the immune mechanism of this therapy is unclear. Forty NA‐experienced CHB patients were enrolled into this study. The frequencies of peripheral blood natural killer (NK) cells, dendritic cells (DCs), CD4 + T cells, CD8 + T cells, T helper (Th) cells, regulatory T cells (Treg ), B cells and follicular T helper (Tfh) cells were evaluated by flow cytometry. Seven of the 40 patients converted to peg‐IFN‐α combined with NA treatment, while the other 33 continued to NA therapy. The decrease in HBsAg was more pronounced in the combination treatment group, and only patients receiving combination treatment achieved HBsAg loss. The frequency and absolute number of CD56 bright NK cells in the combination treatment group increased significantly compared with the NA treatment group, whereas the CD56 dim NK cells were decreased. In the NA treatment group, the proportions of CD4 + TN, CD8 + TN, CD19 + B and cytotoxic T lymphocyte antigen‐4 (CTLA‐4) + CD4 + T cells were increased, while the proportions of CD4 + TEM, CD8 + TEM, CD25 + CD4 + Treg, CD25 high CD4 + Treg, CD127 low CD25 + Treg, programmed cell death 1 (PD‐1) + CD4 + T, PD‐1 + CD8 + T, CTLA‐4 + CD8 + T, CCR4 + CD25 + Treg and CCR4 + CD25 high Treg cells were decreased after therapy. For NA‐experienced CHB patients who achieved low HBsAg levels, combination treatment is more likely to result in HBsAg decline and HBsAg clearance by increasing the activity of CD56 bright NK cells. Abstract : For NA‐experienced CHB patients who achieved low HBsAg levels, a combination of Peg‐IFN‐α and NA therapy is more likely to result in HBsAg decline and HBsAg clearance by increasing the activity of CD56briNK cells. And NA therapy may restore partial immune status in CHB patients through down‐regulating the expression of CCR4 and reducing the immunosuppressive effect of Treg cells.